High‐Performance Strain Sensors Based on Organohydrogel Microsphere Film for Wearable Human–Computer Interfacing. Issue 6 (23rd December 2022) - Zhai, Kankan; Wang, Hao; Ding, Qiongling; Wu, Zixuan; Ding, Minghui; Tao, Kai; Yang, Bo‐Ru; Xie, Xi; Li, Chunwei; Wu, Jin
Abstract: Stretchable hydrogel‐based strain sensors suffer from limited sensitivity, which urgently requires further breakthroughs for precise and stable human‐computer interaction. Here, an efficient microstructural engineering strategy is proposed to significantly enhance the sensitivity of hydrogel‐based strain sensors by sandwiching an emulsion‐polymerized polyacrylamide organohydrogel microsphere membrane between two Ecoflex films, which are accompanied by crack generation and propagation effects upon stretching. Consequently, the as‐developed strain sensor exhibits ultrahigh sensitivity (gauge factor (GF) of 1275), wide detection range (100% strain), low hysteresis, ultralow detection limit (0.05% strain), good fatigue resistance, and low fabrication cost. In addition, the sensor features good water, dehydration, and frost resistance, enabling real‐time strain monitoring in various complex conditions due to the encapsulation of Ecoflex film and the addition of glycerol and KCl. Through further structural manipulation, the device achieves superior response to tiny strains, with a GF value of 98.3 in the strain range of less than 1.5%. Owing to the high strain sensing performance, the sensor is able to detect various human activities from swallowing to finger bending even under water. On this basis, a wireless sensing system with apnea warning and single‐channel gesture recognition capabilities is successfully demonstrated, demonstrating its great promise as wearable electronics. Abstract : An ultrasensitive, stretchable, and environmental‐tolerant strain sensor based on crack mechanism with an Ecoflex‐microspheres‐Ecoflex sandwich structure is created successfully. It features ultra‐high sensitivity (gauge factor: 1275), wide detection range (0–100%), ultralow detection limit, wide operating temperature range, and good waterproofness. A wireless monitoring system is also developed, providing a more effective strategy to realize human–computer interfacing.